A Combined Study of Continuities and Boundedness in Neutrosophic Pseudo-Normed Linear Spaces (European Journal of Pure and Applied Mathematics, 2025)
In this work, we investigate various notions of neutrosophic boundedness and continuity within the framework of neutrosophic pseudo normed linear spaces. Specifically, we introduce and analyze different types of neutrosophic continuity such as pointwise, uniform, and sequential neutrosophic continuity and examine their interrelationships. We also explore several forms of neutrosophic boundedness and establish connections between boundedness and continuity under neutrosophic settings. Illustrative examples are provided to demonstrate the applicability of the introduced concepts.